Efficacy of the oral rabies virus vaccine strain SPBN GASGAS in foxes and raccoon dogs. Issue 33 (2nd August 2019) - Freuling, Conrad M.; Eggerbauer, Elisa; Finke, Stefan; Kaiser, Christiane; Kaiser, Christian; Kretzschmar, Antje; Nolden, Tobias; Ortmann, Steffen; Schröder, Charlotte; Teifke, Jens P.; Schuster, Peter; Vos, Ad; et al.
Highlights: The oral rabies virus vaccine SPBN GASGAS is efficacious in wildlife target species. SPBN GASGAS induces a long-lasting protective immunity in foxes and raccoon dogs. The kinetics of humoral immune response in both target species was similar. There was strong immune response as measured by ELISA but not in RFFIT. SPBN GASGAS meets the requirements of European Pharmacopoeia monograph No. 0746/2014. Abstract: To test the immunogenicity and efficacy of a new oral rabies virus vaccine strain SPBN GASGAS in wildlife target species, one group of foxes and two groups of raccoon dogs were offered a bait containing 1.7 ml of the vaccine (10 6.6  FFU/ml; 10 6.8  FFU/dose) and subsequently challenged approximately 180 days later with a fox rabies virus isolate. One group of raccoon dogs (n = 30) received the same challenge dose (10 0.7  MICLD50 /ml) as the red foxes (n = 29). The other group with raccoon dogs (n = 28) together with 8 animals that received the vaccine dose by direct instillation into the oral cavity (DIOC) were infected with a 40-fold higher dose of the challenge virus (10 2.3  MICLD50 /ml). All but one of the 29 vaccinated foxes survived the challenge infection; meanwhile all 12 control foxes succumbed to rabies. Twenty-eight of 30 vaccinated raccoon dogs challenged with the same dose survived the infection, however only six of 12 control animals succumbed. When the higher challenge dose was administered, all 12 control animals died from rabies and all 36 vaccinated animals (28 baited plus 8 DIOC) survived. Blood samples were collected at different time points post vaccination and examined by both RFFIT and ELISA. The kinetics of the measured immune response was similar for both species, although in RFFIT slightly higher values were observed in foxes than in raccoon dogs. However, the immune response as measured in ELISA was identical for both species. The oral rabies virus vaccine SPBN GASGAS meets the efficacy requirements for live rabies virus vaccines as laid down by the European Pharmacopoeia.